HOW THALICTRUM FOETIDUM EXTRACT INFLUENCES THE LIPID PEROXIDE OXIDATION AND ANTIOXIDANT SYSTEM IN RATS SUBJECTED TO CHRONIC IMMOBILISATION STRESS - Savelyeva E.V.; Vladymyrova I.V.; Lukianova L.V. (Scientific Journal of Pedagogy and Economics, 2020)
The experiment showed a potential correction of the free radical oxidation in the rats’ membrane lipids by means of oral injection of Thalictrum Foetidum aqueous extract, contains a complex of natural antioxidants. The experimental animals were divided into 6 groups (6 animals per group). The experimental animals from group 1 and the animals from group 2, which had been subjected to stress by immobilization for 5 hours, were given 1.5 ml of distil water orally/intragastrically. The animals from group 3, 4, 5 and 6 were given 0.5 ml, 1,0 ml, 1,5 ml and 2,0 ml correspondingly of Thalictrum Foetidum extract orally/intragastrically every day an 1 hour before stress exposition. The animals from all the groups were decapitated under ether anesthetic 5 hours after simulating immobilization stress, notably in the condition of the maximum stress exposition. Blood serum was used for the experiment. There was estimated lipid peroxide oxidation and the condition of the antioxidant system by the spectrophotometric method. For some chances to be observed in the indicators under research, the latter were determined in the control and experimental animals after 5, 15 and 30 days. According to the experimental results, only the 15th and the 30th day, i. e. under chronic stress, show a statistically credible reduction in these indicators as to immobilization stress, approximating the control groups. Analyzing the results of the experiment, we may conclude that Thalictrum Foetidum liquid extract has a rather gentle effect on the lipid peroxide oxidation and antioxidant system under immobilization stress.